HUBUNGAN ANTARA KONTROL DIRI DAN REGULASI EMOSI DENGAN PERILAKU AGRESIF SISWA SMP - Aulia Rayyani, Shafa; Christiana, Elisabeth (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Aggressive behavior in junior high school students is a common phenomenon and has the potential to hinder adolescents' social and emotional development. Individual responses are influenced by self-control and the ability to regulate emotions adaptively. This study aims to analyze the relationship between self-control and emotional regulation with aggressive tendencies in junior high school students. This study was conducted using quantitative methods to examine the relationship between variables. The study participants were 8th-grade students of SMPN 40 Surabaya, with a sample size of 80 students determined using the Slovin formula with a 10% margin of error. The data collection instrument was a Likert scale questionnaire that met the instrument's eligibility requirements. Data analysis was conducted using the normality assumption test, Pearson correlation, and multiple correlations. The results of the analysis showed a moderate relationship between self-control and aggressive tendencies. In addition, emotional regulation also showed a strong correlation with aggressive tendencies. The results of the multiple correlation analysis indicated that both variables were related to students' levels of aggressive behavior. These findings suggest that strengthening individual capacity to manage emotions contributes to a decrease in aggressive tendencies in adolescents. Therefore, self-control and emotional regulation need to be integrated into student mentoring programs at schools to support the development of more adaptive student behavior.